Implementasi Sistem Pelayanan Rakyat Sidoarjo ( SIPRAJA ) di Desa Banjarbendo Kecamatan Sidoarjo Kabupaten Sidoarjo - Aprilia, Veny Alfi; Sukmana, Hendra (Jurnal Noken: Ilmu-Ilmu Sosial, 2023)
The purpose of this study is to describe and analyze the Implementation of the Sidoarjo People's Service System (SIPRAJA) in Banjarbendo Village, Sidoarjo District, Sidoarjo Regency. In this study using a qualitative descriptive research method. Sources of data obtained from interviews, observations, literature studies. indicators in this study using communication, resources, disposition, bureaucratic structure. This research focuses on the Implementation of the Sidoarjo People's Service System (SIPRAJA) in Banjarbendo Village, Sidoarjo District, Sidoarjo Regency. The results of this study indicate that the implementation of sipraja in Banjarbendo Village, Sidoarjo District, Sidoarjo Regency is considered to be lacking in outreach to the people of Banjarbendo Village regarding services using SIPRAJA. So far, the financial resources to support the existence of the Sidoarjo People's Service System are still lacking because it has never been budgeted for. This makes the implementation of the Sidoarjo People's Service System (SIPRAJA) in Banjarbendo Village not optimal and effective.